The Influence of Service Quality and Customer Satisfaction on Customer Loyalty with Customer Engagement as Mediation: a Study at “Kopi Dari Hati”, Madiun - Deriandara, Rakellita; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to examine the methods used by Kopi Dari Hati in Madiun to engage their customers in relation to the following: service quality, customer satisfaction, and customer loyalty. One hundred clients made up the sample for the study. Test results were analyzed using the SmartPLS 4.0 tool, which included assessing the outer and inner models as well as doing hypothesis testing. One study found no significant relationship between service quality and customer loyalty, another found no significant relationship between customer satisfaction and customer loyalty either. However, the studies did find that customer engagement had a positive and significant effect on customer loyalty. The studies also found that service quality had a positive and significant effect on customer engagement, customer satisfaction had a positive and significant effect on customer engagement as well. Lastly, the studies found that customer engagement in Madiun City's Kopi Dari Hati mediated the relationship between service quality and customer loyalty. (7) In Madiun City, the mediation effect of Kopi Dari Hati's customer participation between consumer enjoyment and loyalty is evident.